Realities and impacts of climate change - Zieger, Lee (Callisto Reference, 2015)
The earth is the only planet where life exists. The evolution of human life was only possible due to its favorable environmental conditions i.e. availability of water, oxygen and suitable temperature. Climate change is a significant and lasting change in the statistical distribution of weather patterns over periods ranging from decades to millions of years. Hence, the field of climate control requires special attention to control the rise in atmospheric temperature by controlling the emission of greenhouse gases. There is a need to conserve natural resources and look for some alternative to these resources. The book provides basic information and facts about climate change with special focus on its impact on vegetation, adapting rain fed agriculture, climate change assessment due to soil moisture change and adaptation to future climate change for crop farms. Additionally, latest technologies applied and adopted to reduce the impact of climate change are also discussed.